Laminate contacting fuel
Patent Information
- Application Number
- JP2024131902
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-14
- Filing Date
- 2024-08-08
- Publication Date
- 2025-02-27
- Estimated Expiration
- 2044-08-08
AI Technical Summary
【0006】 本開示によれば、炭素原子、水素原子および酸素原子のみからなり、かつ、カルボニル基またはエーテル結合を有する化合物を含有する燃料に対して、優れた燃料低透過性を示す積層体を提供することができる。
Smart Images

Figure 2025027454000001 
Figure 2025027454000002 
Figure 2025027454000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to laminates that come into contact with fuel. [Background technology]
[0002] Patent Document 1 describes a laminate structure composed of two or more layers, including at least (A) layer (a) made of an aliphatic polyamide, and (B) layer (b) made of a semi-aromatic polyamide composed of diamine units containing 60 mol % or more of aliphatic diamine units having 9 to 13 carbon atoms relative to all diamine units, and dicarboxylic acid units containing 50 mol % or more of terephthalic acid and / or naphthalenedicarboxylic acid units relative to all dicarboxylic acid units, and wherein layer (b) is disposed as the innermost layer. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2005 / 102694 Summary of the Invention [Problem to be solved by the invention]
[0004] An object of the present disclosure is to provide a laminate that exhibits excellent low fuel permeability to a fuel that is composed only of carbon atoms, hydrogen atoms, and oxygen atoms and contains a compound having a carbonyl group or an ether bond. [Means for solving the problem]
[0005] According to the present disclosure, there is provided a laminate to be in contact with a fuel, the fuel containing at least a compound (1) consisting of only carbon atoms, hydrogen atoms, and oxygen atoms and having a carbonyl group or an ether bond, the laminate including at least a non-fluorinated polymer layer containing at least one non-fluorinated polymer selected from the group consisting of an ethylene / vinyl alcohol copolymer and an aromatic polyamide. Effect of the Invention
[0006] According to the present disclosure, it is possible to provide a laminate that exhibits excellent low fuel permeability to a fuel that is composed only of carbon atoms, hydrogen atoms, and oxygen atoms and that contains a compound having a carbonyl group or an ether bond. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] Specific embodiments of the present disclosure will be described in detail below, but the present disclosure is not limited to the following embodiments.
[0008] 2. Description of the Related Art Laminates that exhibit low fuel permeability to gasoline or low fuel permeability to alcohol-containing gasoline are conventionally known.
[0009] For example, Patent Document 1 describes that the fuel permeability coefficient of a laminated structure having the above-mentioned configuration was measured for alcohol-containing gasoline, which is a mixture of Fuel C (iso-octane / toluene = 50 / 50 volume ratio) and ethanol in a volume ratio of 90 / 10.
[0010] However, there has been no sufficient study to date as to what kind of laminate structure is required to suppress the permeation of fuels that contain compounds that consist only of carbon atoms, hydrogen atoms, and oxygen atoms and have carbonyl groups or ether bonds.
[0011] It has now been found that by incorporating into the laminate a non-fluorinated polymer layer containing at least one non-fluorinated polymer selected from the group consisting of ethylene / vinyl alcohol copolymers and aromatic polyamides, the laminate exhibits surprisingly low fuel permeability to fuels that consist only of carbon, hydrogen and oxygen atoms and contain compounds having carbonyl groups or ether bonds.
[0012] That is, the laminate of the present disclosure is a laminate that comes into contact with a fuel, which consists only of carbon atoms, hydrogen atoms, and oxygen atoms and contains at least a compound (1) having a carbonyl group or an ether bond, and which has at least a non-fluorinated polymer layer containing at least one non-fluorinated polymer selected from the group consisting of an ethylene / vinyl alcohol copolymer and an aromatic polyamide.
[0013] The configuration of the laminate of the present disclosure will be described in detail below.
[0014] (fuel) The laminate of the present disclosure is used in contact with a fuel that is composed only of carbon, hydrogen, and oxygen atoms and contains at least a compound (1) having a carbonyl group or an ether bond. In one embodiment, the laminate of the present disclosure is used to suppress the permeation of a fuel that is composed only of carbon, hydrogen, and oxygen atoms and contains at least a compound (1) having a carbonyl group or an ether bond. In one embodiment, the laminate of the present disclosure is a tube or hose, and is used to distribute and / or suppress the permeation of a fuel that is composed only of carbon, hydrogen, and oxygen atoms and contains at least a compound (1) having a carbonyl group or an ether bond. That is, the present disclosure includes the use of a laminate (tube or hose) for distributing a fuel containing at least a compound (1) consisting only of carbon atoms, hydrogen atoms, and oxygen atoms and having a carbonyl group or an ether bond, and / or for suppressing the permeation of the fuel. The present disclosure also includes a method for distributing a fuel containing at least a compound (1) consisting only of carbon, hydrogen, and oxygen atoms and having a carbonyl group or an ether bond, comprising using a laminate (tube or hose) in contact with the fuel.
[0015] Compound (1) may be a compound synthesized from hydrogen and carbon dioxide. Compounds synthesized from hydrogen and carbon dioxide are also called synthetic fuels, and are expected to contribute to reducing carbon dioxide emissions. The inventors' studies have revealed that conventional laminates can suppress the permeation of conventional fuels such as gasoline, diesel fuel, and alcohol fuel, but cannot sufficiently suppress the permeation of such synthetic fuels. That is, compound (1) exhibits permeability different from that of conventional fuels such as gasoline, diesel fuel, and alcohol fuel. Therefore, conventional knowledge cannot be utilized when selecting the layer structure of a laminate used in contact with a fuel containing compound (1). Therefore, as a result of intensive studies by the inventors, a laminate exhibiting low fuel permeability even for compound (1) has been found.
[0016] Compound (1) is preferably at least one selected from the group consisting of carbonate esters, linear ethers, and cyclic ethers, more preferably at least one selected from the group consisting of carbonate esters and cyclic ethers, and even more preferably carbonate esters.
[0017] Examples of the compound (1) include dimethyl carbonate, diethyl carbonate, dimethyl ether, methyl tert-butyl ether (MTBE), oxymethylene dimethyl ether, and 1-3 dioxolane. The fuel contains one or more of these compounds. Of these, at least one compound selected from the group consisting of dimethyl carbonate and diethyl carbonate is preferred as the compound (1).
[0018] The fuel may contain only the compound (1), or may contain the compound (1) and other fuels.
[0019] The fuel, for example, A fuel containing only compound (1); A fuel containing compound (1) and alcohol; A fuel containing compound (1) and gasoline; A fuel containing compound (1), alcohol and gasoline; A fuel containing compound (1) and diesel fuel (light oil), etc.
[0020] The content of compound (1) in the fuel may be 0.1 to 100% by volume. The content of compound (1) in the fuel may be 1% by volume or more, 5% by volume or more, or 10% by volume or more. The content of compound (1) in the fuel may be 90% by volume or less, 80% by volume or less, 60% by volume or less, 40% by volume or less, or 20% by volume or less.
[0021] In one embodiment, the fuel contains the compound (1) and an alcohol. The laminate of the present disclosure also exhibits excellent low permeability to a fuel containing the compound (1) and an alcohol.
[0022] The alcohol is preferably an alcohol having 1 to 5 carbon atoms, more preferably at least one selected from the group consisting of methanol, ethanol, propanol and butanol, and further preferably at least one selected from the group consisting of methanol and ethanol.
[0023] The alcohol content in the fuel may be 10 to 99.9% by volume. The alcohol content in the fuel may be 20% by volume or more, 40% by volume or more, or 80% by volume or more. The alcohol content in the fuel may be 99% by volume or less, 95% by volume or less, or 90% by volume or less.
[0024] When the alcohol in the fuel is methanol, the content thereof may be 10 to 99.9% by volume. The content of methanol in the fuel may be 80% by volume or less, 50% by volume or less, 30% by volume or less, or 20% by volume or less.
[0025] In one embodiment, the fuel contains the compound (1) and gasoline. The laminate of the present disclosure also exhibits excellent low permeability to the fuel containing the compound (1) and gasoline.
[0026] The gasoline may be obtained by refining crude oil. The boiling point of gasoline is generally 30 to 220°C.
[0027] The gasoline content in the fuel may be 10 to 99.9% by volume. The gasoline content in the fuel may be 20% by volume or more, 40% by volume or more, or 80% by volume or more. The gasoline content in the fuel may be 99% by volume or less, 95% by volume or less, or 90% by volume or less.
[0028] In one embodiment, the fuel does not include diesel fuel (gas oil). Diesel fuel may be obtained by refining crude oil. Diesel fuel generally has a boiling point greater than 220°C and less than or equal to 350°C.
[0029] In one embodiment, the fuel contains compound (1) and diesel fuel (light oil).
[0030] Conventionally, aliphatic polyamides have been used as materials for forming tubes or hoses for diesel fuel, because they have excellent acid resistance, alkali resistance, hydrolysis resistance, physical properties, etc. Unlike gasoline and alcohol-containing fuels, diesel fuel (light oil) does not easily permeate aliphatic polyamide tubes, and therefore no consideration has been given to selecting materials from the perspective of suppressing the permeation of diesel fuel.
[0031] Compound (1) may be a compound synthesized from hydrogen and carbon dioxide. Compounds synthesized from hydrogen and carbon dioxide are also called synthetic fuels, and are expected to contribute to reducing carbon dioxide emissions. Unlike gasoline and alcohol-containing fuels, diesel fuel (diesel oil) is less likely to permeate aliphatic polyamide tubes. However, it has been found that when such synthetic fuels are blended with diesel fuel, the fuel permeates the tube and diffuses to the outside. As a result of intensive research by the present inventors, a laminate exhibiting low fuel permeability to diesel fuel and fuels containing compound (1) has been found.
[0032] That is, it has now been found that by incorporating into a laminate a non-fluorinated polymer layer containing at least one non-fluorinated polymer selected from the group consisting of ethylene / vinyl alcohol copolymers and aromatic polyamides, the laminate exhibits surprisingly low fuel permeability to diesel fuel and fuels containing compounds consisting only of carbon, hydrogen and oxygen atoms and having carbonyl groups or ether bonds.
[0033] Diesel fuel may be obtained by refining crude oil. Diesel fuel generally has a boiling point greater than 220°C and less than or equal to 350°C.
[0034] The content of diesel fuel in the fuel may be 10 to 99.9% by volume. The content of diesel fuel in the fuel may be 20% by volume or more, 40% by volume or more, or 80% by volume or more. The content of diesel fuel in the fuel may be 99% by volume or less, 95% by volume or less, or 90% by volume or less.
[0035] In one embodiment, the fuel does not include gasoline. Gasoline may be obtained by refining crude oil. The boiling point of gasoline is generally 30 to 220°C.
[0036] In one embodiment, the fuel does not contain alcohol. Examples of the alcohol include alcohols having 1 to 5 carbon atoms.
[0037] (Non-fluorinated polymer layer (A)) The laminate of the present disclosure comprises at least a non-fluorinated polymer layer (A) containing at least one non-fluorinated polymer (A) selected from the group consisting of an ethylene / vinyl alcohol copolymer and an aromatic polyamide.
[0038] As described above, the laminate of the present disclosure includes at least the non-fluorinated polymer layer (A), and since the non-fluorinated polymer layer (A) contains at least one non-fluorinated polymer (A) selected from the group consisting of ethylene / vinyl alcohol copolymers and aromatic polyamides, it exhibits excellent low fuel permeability to fuels that consist of only carbon atoms, hydrogen atoms, and oxygen atoms and contain a compound having a carbonyl group or an ether bond. Surprisingly, when a non-fluorinated polymer other than ethylene / vinyl alcohol copolymers and aromatic polyamides, for example, an aliphatic polyamide such as PA12, is used, sufficient low fuel permeability cannot be obtained.
[0039] The ethylene / vinyl alcohol copolymer used in the laminate of the present disclosure may be a thermoplastic resin. The ethylene / vinyl alcohol copolymer is obtained by saponifying an ethylene / vinyl acetate copolymer obtained from ethylene and vinyl acetate. The blending ratio of the ethylene and vinyl acetate to be copolymerized is appropriately determined according to the ratio of the moles of vinyl acetate units defined by the formula described below.
[0040] The ethylene / vinyl alcohol copolymer preferably has a vinyl acetate unit content of X mole % and a degree of saponification of Y mole % satisfying X×Y / 100≧7. If X×Y / 100<7, the interlayer adhesive strength may be insufficient. X×Y / 100≧10 is more preferable. The value of X×Y / 100 is an index of the content of hydroxyl groups in the ethylene / vinyl alcohol copolymer, and a large value of X×Y / 100 means that the ethylene / vinyl alcohol copolymer has a high content of hydroxyl groups.
[0041] Hydroxyl groups are groups that can participate in adhesion between the EVOH layer and the other material to be laminated, and when the ethylene / vinyl alcohol copolymer has a high content of hydroxyl groups, the interlayer adhesion in the laminate is improved. In this disclosure, the above-mentioned "other material to be laminated" refers to a material that is in contact with the material to be laminated.
[0042] In the present disclosure, the term "X mol % of vinyl acetate units" refers to the ratio of the number of moles [Ni] of vinyl acetate units to the total number of moles [N] of ethylene and vinyl acetate added in the molecule of an ethylene / vinyl alcohol copolymer, and is expressed by the following formula: Xi(%)=(Ni / N)×100 The vinyl acetate unit X mol % is a value obtained by measurement using infrared absorption spectroscopy (IR).
[0043] In the present disclosure, the term "vinyl acetate unit" refers to a portion of the molecular structure of an ethylene / vinyl alcohol copolymer that is derived from vinyl acetate. The vinyl acetate unit may be saponified and have a hydroxyl group, or may be unsaponified and have an acetoxyl group.
[0044] The "saponification degree" is a percentage that represents the ratio of the number of saponified vinyl acetate units to the total number of saponified vinyl acetate units and the number of unsaponified vinyl acetate units. The saponification degree is a value obtained by measurement using infrared absorption spectroscopy (IR).
[0045] Examples of ethylene / vinyl alcohol copolymers in which X and Y satisfy the above formula include commercially available products such as EVAL F101 (manufactured by Kuraray Co., Ltd., vinyl acetate unit X=68.0 mol %; saponification degree Y=95%; X×Y / 100=64.6), MERSEN H6051 (manufactured by Tosoh Corporation, vinyl acetate unit X=11.2 mol %; saponification degree Y=100%; X×Y / 100=11.2), and Technolink K200 (manufactured by Taoka Chemical Co., Ltd., vinyl acetate unit X=11.2 mol %; saponification degree Y=85%; X×Y / 100=9.52).
[0046] The ethylene / vinyl alcohol copolymer preferably has an MFR of 0.5 g / 10 min or more at 200 ° C., and preferably has an MFR of 100 g / 10 min or less. If the MFR is less than 0.5 g / 10 min or more than 100 g / 10 min, the difference between the melt viscosity of the ethylene / vinyl alcohol copolymer and the melt viscosity of the mating material tends to become large, and there is a possibility that unevenness may occur in the thickness of each layer, which is not preferable. The preferred lower limit is 1 g / 10 min, and the preferred upper limit is 50 g / 10 min.
[0047] The aromatic polyamide used in the laminate of the present disclosure may be a thermoplastic resin. In the present disclosure, the aromatic polyamide includes semi-aromatic polyamide and fully aromatic polyamide. In one embodiment, the aromatic polyamide is a semi-aromatic polyamide containing an aliphatic diamine unit and an aromatic dicarboxylic acid unit.
[0048] Examples of the aliphatic diamine include 1,2-ethanediamine, 1,3-propanediamine, 1,4-butanediamine, 1,5-pentanediamine, 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 1,11-undecanediamine, and 1,12-dodecanediamine. Of these, 1,6-hexanediamine and 1,9-nonanediamine are preferred.
[0049] Examples of the aromatic dicarboxylic acid include terephthalic acid, phthalic acid, isophthalic acid, and naphthalenedicarboxylic acid, and among these, terephthalic acid is preferred.
[0050] The melting point of the semi-aromatic polyamide is preferably 200°C or higher, more preferably 250°C or higher, and preferably 350°C or lower.
[0051] Of the aromatic polyamides, polyamide 6T and polyamide 9T are preferred, and polyamide 9T is more preferred.
[0052] The non-fluorinated polymer layer (A) may contain various additives, such as stabilizers such as heat stabilizers, reinforcing agents, fillers, ultraviolet absorbers, pigments, etc., within the scope of the present disclosure. By using such additives, the properties of the non-fluorinated polymer, such as heat stability, surface hardness, abrasion resistance, electrostatic property, weather resistance, etc., can be improved.
[0053] In one embodiment, the non-fluorinated polymer layer (A) is not electrically conductive. In one embodiment, the non-fluorinated polymer layer (A) does not contain a conductive filler.
[0054] (Conductive layer (N1)) The laminate of the present disclosure has electrical conductivity and may further include a conductive layer (N1) containing a non-fluorinated polymer (N1). By including the conductive layer (N1), it is possible to prevent the laminate from being charged even if static electricity is generated due to friction between the laminate and fuel.
[0055] The non-fluorinated polymer (N1) is a polymer that does not have fluorine atoms. As the non-fluorinated polymer (N1), a wide variety of polymers known as thermoplastic resins can be used. Examples of the non-fluorinated polymer (N1) include polyamide resins, polyolefin resins, vinyl chloride resins, polyurethane resins, polyester resins, polyaramid resins, polyimide resins, polyamideimide resins, polyphenylene oxide resins, polyacetal resins, polycarbonate resins, acrylic resins, styrene resins, acrylonitrile / butadiene / styrene resins (ABS), cellulose resins, polyether ether ketone resins (PEEK), polysulfone resins, polyether sulfone resins (PES), polyetherimide resins, ethylene / vinyl alcohol copolymer resins, polyphenylene sulfide resins, polybutylene naphthalate resins, polybutylene terephthalate resins, and polyphthalamide (PPA).
[0056] The melting point of the non-fluorinated polymer (N1) is preferably 50° C. or higher, more preferably 100° C. or higher, even more preferably 150° C. or higher, still more preferably 200° C. or higher, particularly preferably 250° C. or higher, and preferably 400° C. or lower, more preferably 350° C. or lower, still more preferably 300° C. or lower, still more preferably 250° C. or lower.
[0057] As the non-fluorinated polymer (N1) constituting the conductive layer (N1), an aromatic polyamide is particularly preferred. As the aromatic polyamide, the same aromatic polyamide as that constituting the non-fluorinated polymer layer (A) can be used, and the same aromatic polyamide is preferred.
[0058] In one embodiment, the aromatic polyamide constituting the conductive layer (N1) is an aromatic polyamide containing an aliphatic diamine unit and an aromatic dicarboxylic acid unit.
[0059] As the aromatic polyamide constituting the conductive layer (N1), polyamide 6T and polyamide 9T are preferable, and polyamide 9T is more preferable.
[0060] The conductive layer (N1) preferably contains a conductive filler, which easily imparts conductivity to the conductive layer (N1), and further prevents the laminate from being charged even if static electricity is generated due to friction between the laminate and fuel.
[0061] The conductive filler is not particularly limited, and examples thereof include conductive simple substance powders or conductive simple substance fibers of metals, carbon, etc.; powders of conductive compounds such as zinc oxide; and powders that have been surface-treated to be conductive.
[0062] The conductive elemental powder or conductive elemental fiber is not particularly limited, and examples thereof include metal powders such as copper and nickel; metal fibers such as iron and stainless steel; carbon black, carbon fibers, carbon fibrils, carbon nanotubes, and carbon nanohorns, as described in JP-A-3-174018, etc.
[0063] The surface-conductively treated powder is a powder obtained by subjecting the surface of a non-conductive powder such as glass beads or titanium oxide to a conductive treatment. The method of the conductive treatment is not particularly limited, and examples thereof include metal sputtering and electroless plating. Among the above-mentioned conductive fillers, carbon black is preferably used because it is advantageous from the viewpoint of economy.
[0064] The amount of the conductive filler is appropriately determined based on the type of non-fluorinated polymer (N1), the conductive performance required for the laminate, molding conditions, etc., but is preferably 1 part by mass or more and preferably 30 parts by mass or less per 100 parts by mass of the non-fluorinated polymer (N1). A more preferred lower limit is 5 parts by mass, and a more preferred upper limit is 20 parts by mass.
[0065] The conductive layer (N1) may contain, in addition to the conductive filler, various additives such as reinforcing agents, bulking agents, ultraviolet absorbers, pigments, etc., within the scope of the present disclosure. By using such additives, the properties of the conductive layer (N1), such as surface hardness, abrasion resistance, electrostatic property, weather resistance, etc., can be improved.
[0066] When the laminate of the present disclosure includes a conductive layer (N1), the conductive layer (N1) is preferably configured to come into contact with the fuel. By forming the contact surface between the laminate and the fuel with the conductive layer (N1), charging of the laminate can be further prevented even if static electricity is generated by friction between the laminate and the fuel.
[0067] (Fluororesin layer (F)) The laminate of the present disclosure may further include a fluororesin layer (F) containing a fluororesin. The fluororesin is a partially crystalline fluoropolymer, and is a fluoroplastic, not a fluororubber. The fluororesin has a melting point and has thermoplasticity. The fluororesin may be melt-processable or non-melt-processable, but is preferably a melt-processable fluororesin because it can be used to produce a tube with high productivity by melt extrusion molding.
[0068] In this disclosure, melt processable means that the polymer can be melted and processed using conventional processing equipment such as extruders, injection molding machines, etc. Thus, melt processable fluororesins typically have a melt flow rate of 0.01 g / 10 min or more and 500 g / 10 min or less.
[0069] Examples of melt-processable fluororesins include tetrafluoroethylene (TFE) / perfluoro(alkyl vinyl ether) (PAVE) copolymers, tetrafluoroethylene (TFE) / hexafluoropropylene (HFP) copolymers, TFE / ethylene copolymers (ETFE), TFE / ethylene / HFP copolymers, polymers containing chlorotrifluoroethylene (CTFE) units, polyvinylidene fluoride (PVdF), TFE / vinylidene fluoride (VdF) copolymers (VT), polyvinyl fluoride (PVF), TFE / HFP / VdF copolymers, and the like.
[0070] Examples of PAVE include perfluoro(methyl vinyl ether) (PMVE), perfluoro(ethyl vinyl ether) (PEVE), and perfluoro(propyl vinyl ether) (PPVE). Among them, PPVE is preferable. These can be used alone or in combination of two or more.
[0071] The fluororesin may have polymerization units based on other monomers in an amount that does not impair the essential properties of each fluororesin. The other monomers may be appropriately selected from, for example, TFE, HFP, ethylene, propylene, perfluoro(alkyl vinyl ether), perfluoroalkyl ethylene, hydrofluoroolefin, fluoroalkyl ethylene, perfluoro(alkyl allyl ether), etc.
[0072] The melting point of the fluororesin is preferably 160°C or higher, more preferably 190°C or higher, even more preferably 230°C or higher, particularly preferably 240°C or higher, and preferably less than 324°C, more preferably 320°C or lower, even more preferably 300°C or lower, particularly preferably 280°C or lower, and most preferably 260°C or lower.
[0073] The melt flow rate (MFR) of the fluororesin at any temperature (e.g., 265°C or 297°C) in the range of 230 to 350°C, which is a general molding temperature range, is preferably 0.5 g / 10 min or more, more preferably 2.0 g / 10 min or more, even more preferably 5.0 g / 10 min or more, particularly preferably 10 g / 10 min or more, most preferably 15 g / 10 min or more, preferably 100 g / 10 min or less, more preferably 50 g / 10 min or less, even more preferably 40 g / 10 min or less, and particularly preferably 35 g / 10 min or less. The melt flow rate can be determined, for example, by using a melt indexer to measure the mass (g) of the fluororesin flowing out from a nozzle with an inner diameter of 2 mm and a length of 8 mm per unit time (10 minutes) at any temperature (e.g., 265°C or 297°C) and any load (e.g., 2.16 kg or 5 kg).
[0074] The fluororesin is preferably at least one selected from the group consisting of TFE / perfluoro(alkyl vinyl ether) (PAVE) copolymer, tetrafluoroethylene (TFE) / hexafluoropropylene (HFP) copolymer, TFE / ethylene copolymer (ETFE), TFE / ethylene / HFP copolymer, polymers containing CTFE units, and tetrafluoroethylene / hexafluoropropylene / vinylidene fluoride copolymer (THV), more preferably at least one selected from the group consisting of TFE / ethylene copolymer (ETFE), TFE / ethylene / HFP copolymer, and polymers containing CTFE units, and more preferably at least one selected from the group consisting of TFE / ethylene copolymer (ETFE) and TFE / ethylene / HFP copolymer.
[0075] In the present disclosure, the composition of the fluororesin can be calculated by an appropriate combination of NMR, FT-IR, elemental analysis, and X-ray fluorescence analysis depending on the type of monomer.
[0076] The TFE / HFP copolymer preferably has a TFE / HFP mass ratio of 80-97 / 3-20, and more preferably 84-92 / 8-16. The TFE / HFP copolymer may be a binary copolymer made of TFE and HFP, or may be a ternary copolymer made of TFE and a monomer copolymerizable with HFP (for example, a TFE / HFP / PAVE copolymer).
[0077] The TFE / HFP copolymer is also preferably a TFE / HFP / PAVE copolymer containing polymerized units based on PAVE. The TFE / HFP / PAVE copolymer preferably has a mass ratio of TFE / HFP / PAVE of 70-97 / 2.9-20 / 0.1-10, and more preferably 81-92 / 5-16 / 0.3-5.
[0078] The TFE / PAVE copolymer preferably has a TFE / PAVE mass ratio of 90-99 / 1-10, and more preferably 92-97 / 3-8.
[0079] ETFE is a copolymer containing ethylene units and TFE units. As ETFE, a copolymer having a molar ratio of TFE units to ethylene units (TFE units / ethylene units) of 20 / 80 or more and 90 / 10 or less is preferred. A more preferred molar ratio is 37 / 63 or more and 85 / 15 or less, and an even more preferred molar ratio is 38 / 62 or more and 80 / 20 or less. The ETFE may be a copolymer of TFE, ethylene, and a monomer copolymerizable with TFE and ethylene. The copolymerizable monomer is a copolymer represented by the following formula: CH2=CX 5 Rf 3 , CF2=CFRf 3 , CF2=CFORf 3 , CH2=C(Rf3 )2 (In the formula, X 5 is H or F, Rf 3 represents a fluoroalkyl group which may contain an ether bond. 3 , CF2=CFORf 3 and CH2=CX 5 Rf 3 Preferably, at least one selected from the group consisting of fluorine-containing vinyl monomers represented by the formula: 4 (In the formula, Rf 4 represents a perfluoroalkyl group having 1 to 5 carbon atoms. 3 is a fluoroalkyl group having 1 to 8 carbon atoms, CH2=CX 5 Rf 3 More preferably, it is at least one selected from the group consisting of fluorine-containing vinyl monomers represented by the following formula: and HFP is even more preferable. The monomer copolymerizable with TFE and ethylene may be an aliphatic unsaturated carboxylic acid such as itaconic acid or itaconic anhydride. In ETFE, the monomer unit copolymerizable with TFE and ethylene is preferably 0.1 mol % or more, more preferably 0.2 mol % or more, and more preferably 10 mol % or less, more preferably 5 mol % or less, and particularly preferably 4 mol % or less.
[0080] The TFE / ethylene copolymer [ETFE] is also preferably a TFE / ethylene / HFP copolymer containing a polymerization unit based on HFP (HFP unit). The TFE / ethylene / HFP copolymer preferably has a TFE / ethylene / HFP molar ratio of 40-65 / 30-59.5 / 0.5-20, more preferably 40-65 / 30-59.5 / 0.5-10.
[0081] The melting point of ETFE is preferably 160°C or higher, more preferably 170°C or higher, even more preferably 180°C or higher, particularly preferably 190°C or higher, preferably less than 324°C, more preferably 320°C or lower, even more preferably 300°C or lower, particularly preferably 280°C or lower, and most preferably 260°C or lower.
[0082] The MFR (265°C) of ETFE is preferably 0.5g / 10min or more, more preferably 2.0g / 10min or more, even more preferably 5.0g / 10min or more, particularly preferably 8g / 10min or more, most preferably 10g / 10min or more, preferably 100g / 10min or less, more preferably 50g / 10min or less, even more preferably 40g / 10min or less, particularly preferably 30g / 10min or less, and most preferably 25g / 10min or less. The measurement of the MFR of ETFE is performed at a temperature of 297°C or 265°C and a load of 5 kg.
[0083] It is also suitable to use the ethylene / tetrafluoroethylene copolymer described in JP-A-2019-90013 as ETFE.
[0084] The polymer containing CTFE units is preferably at least one selected from the group consisting of polychlorotrifluoroethylene [PCTFE] and CTFE copolymers.
[0085] The content of CTFE units in a polymer containing CTFE units is, relative to all monomer units, preferably 1.0 mol % or more, more preferably 5.0 mol % or more, even more preferably 10.0 mol % or more, particularly preferably 15.0 mol % or more, and is preferably 100 mol % or less, more preferably 75.0 mol % or less, even more preferably 50.0 mol % or less, and particularly preferably 30.0 mol % or less, because low fuel permeability is further improved.
[0086] Examples of polymers containing CTFE units include ethylene / chlorotrifluoroethylene (CTFE) copolymers (ECTFE), polychlorotrifluoroethylene (PCTFE), CTFE / tetrafluoroethylene (TFE) copolymers, and TFE / vinylidene fluoride (VdF) / CTFE copolymers (VTC). At least one selected from the group consisting of PCTFE, ethylene / CTFE copolymers, and CTFE / TFE copolymers is preferred, and CTFE / TFE copolymers are more preferred from the viewpoint of low fuel permeability.
[0087] PCTFE includes CTFE homopolymers and polymers containing CTFE units and small amounts of comonomer units.
[0088] The melting point of PCTFE is preferably 150° C. or higher, more preferably 190° C. or higher, and preferably 230° C. or lower, more preferably 217° C. or lower. The melting point is the temperature corresponding to the maximum value in the heat of fusion curve when the temperature is increased at a rate of 10° C. / min using a differential scanning calorimeter [DSC].
[0089] The flow value of PCTFE is preferably 1×10 -4 (cm 3 / sec) or more, preferably 5 × 10 -1 (cm 3 The flow value is the volume of resin extruded per second when PCTFE is melted at 230°C using a Koga type flow tester CFT-500D (manufactured by Shimadzu Corporation) and extruded from a nozzle with a diameter of 1 mm under a load of 100 kg.
[0090] The content of CTFE units in PCTFE is preferably 95 mol % or more, more preferably 98 mol % or more, further preferably 99 mol % or more, and preferably 100 mol % or less.
[0091] The comonomer constituting the comonomer unit that can be contained in PCTFE is not particularly limited as long as it is a monomer copolymerizable with CTFE, and examples thereof include TFE, ethylene, vinylidene fluoride, perfluoroalkyl vinyl ether, and hexafluoroethylene.
[0092] The ethylene / CTFE copolymer (ECTFE) is a copolymer containing ethylene units and CTFE units, and preferably contains 46 to 52 mol% of ethylene units and 54 to 48 mol% of CTFE units relative to the total of the ethylene units and CTFE units. ECTFE may be a binary copolymer consisting of only ethylene units and CTFE units, or may further contain polymerization units based on a monomer copolymerizable with ethylene and CTFE (e.g., a fluoroalkyl vinyl ether (PAVE) derivative). The content of polymerization units based on monomers copolymerizable with ethylene and CTFE is preferably 0.01 mol % or more and 5 mol % or less based on the total of the ethylene units, CTFE units, and polymerization units based on the above-mentioned copolymerizable monomers.
[0093] The MFR (230°C) of ECTFE is preferably 0.5 g / 10 min or more and preferably 100 g / 10 min or less. The MFR of ECTFE is measured at a temperature of 230°C and a load of 2.16 kg.
[0094] The CTFE / TFE copolymer contains CTFE units and TFE units. Particularly preferred CTFE / TFE copolymers include those containing CTFE units, TFE units, and monomer (α) units derived from a monomer (α) copolymerizable with these units.
[0095] The monomer (α) is not particularly limited as long as it is a monomer copolymerizable with CTFE and TFE, and examples thereof include ethylene (Et), VdF, CF2=CF-ORf 1 (In the formula, Rf 1 Perfluoro(alkyl vinyl ether) (PAVE) represented by a perfluoroalkyl group having 1 to 8 carbon atoms, CX 3 X4 =CX 5 (CF2) n X 6 (In the formula, X 3 , X 4 and X 5 are the same or different and are a hydrogen atom or a fluorine atom; X 6 is a hydrogen atom, a fluorine atom, or a chlorine atom; n is an integer of 1 to 10), 2 (In the formula, Rf 2 and alkyl perfluorovinyl ether derivatives represented by the formula (I) (a perfluoroalkyl group having 1 to 5 carbon atoms), among which at least one selected from the group consisting of PAVE, the vinyl monomers and alkyl perfluorovinyl ether derivatives is preferred, and at least one selected from the group consisting of PAVE and HFP is more preferred.
[0096] For PAVE, CF2=CF-ORf 3 (In the formula, Rf 3 represents a perfluoroalkyl group having 1 to 5 carbon atoms.) is preferred, and examples thereof include perfluoro(methyl vinyl ether) [PMVE], perfluoro(ethyl vinyl ether) [PEVE], perfluoro(propyl vinyl ether) [PPVE], perfluoro(butyl vinyl ether), and the like. Among these, at least one selected from the group consisting of PMVE, PEVE, and PPVE is more preferred, and PPVE is even more preferred.
[0097] As the alkyl perfluorovinyl ether derivative, Rf 2 is preferably a perfluoroalkyl group having 1 to 3 carbon atoms, and CF2=CF-OCH2-CF2CF3 is more preferable.
[0098] The ratio of CTFE units to TFE units in the CTFE / TFE copolymer is preferably 15.0 to 90.0 mol % of CTFE units and 85.0 to 10.0 mol % of TFE units, more preferably 15.0 to 50.0 mol % of CTFE units and 85.0 to 50.0 mol % of TFE units, and even more preferably 15.0 to 30.0 mol % of CTFE units and 85.0 to 70.0 mol % of TFE units.
[0099] The CTFE / TFE copolymer preferably contains 90.0 to 99.9 mol% of CTFE units and TFE units in total, and 0.1 to 10.0 mol% of monomer (α) units. If the monomer (α) units are less than 0.1 mol%, the moldability, environmental stress cracking resistance, and fuel cracking resistance tend to be poor, whereas if they exceed 10.0 mol%, the fuel barrier properties, heat resistance, and mechanical properties tend to be poor.
[0100] As the CTFE / TFE copolymer, a CTFE / TFE / PAVE copolymer is particularly preferred.
[0101] In the CTFE / TFE / PAVE copolymer, the above-mentioned PAVE may be perfluoro(methyl vinyl ether) [PMVE], perfluoro(ethyl vinyl ether) [PEVE], perfluoro(propyl vinyl ether) [PPVE], perfluoro(butyl vinyl ether), etc., and among these, at least one selected from the group consisting of PMVE, PEVE and PPVE is preferred, with PPVE being more preferred. In the CTFE / TFE / PAVE copolymer, the PAVE unit preferably accounts for 0.5 mol % or more and 5 mol % or less of the total monomer units.
[0102] The melting point of the CTFE / TFE copolymer is preferably 190°C or higher, more preferably 210°C or higher, even more preferably 220°C or higher, particularly preferably 230°C or higher, and most preferably 240°C or higher, and is preferably less than 324°C, more preferably 320°C or lower, even more preferably 270°C or lower, and most preferably 260°C or lower.
[0103] The MFR (297°C) of the CTFE / TFE copolymer is preferably 0.5 g / 10 min or more, more preferably 2.0 g / 10 min or more, even more preferably 5.0 g / 10 min or more, particularly preferably 7 g / 10 min or more, most preferably 10 g / 10 min or more, preferably 100 g / 10 min or less, more preferably 50 g / 10 min or less, even more preferably 40 g / 10 min or less, particularly preferably 35 g / 10 min or less. The MFR of the CTFE / TFE copolymer is measured at a temperature of 297°C and a load of 5 kg.
[0104] The fluororesin layer (F) is preferably conductive. When the fluororesin layer (F) is conductive, it can prevent the laminate from becoming charged even if static electricity is generated due to friction between the laminate and fuel.
[0105] The fluororesin layer (F) preferably contains a conductive filler, which easily imparts electrical conductivity to the fluororesin layer (F), and prevents the laminate from becoming charged even if static electricity is generated by friction between the laminate and fuel.
[0106] As the conductive filler, the same conductive filler as that which the conductive layer (N1) can contain can be used, and the same conductive filler is preferable.
[0107] The amount of the conductive filler is appropriately determined based on the type of fluororesin, the conductive performance required for the laminate, molding conditions, etc., but is preferably 1 part by mass or more and 30 parts by mass or less per 100 parts by mass of fluororesin. The more preferred lower limit is 5 parts by mass, and the more preferred upper limit is 20 parts by mass.
[0108] The fluororesin layer (F) may contain, in addition to the conductive filler, various additives such as reinforcing agents, bulking agents, ultraviolet absorbers, pigments, etc., within the scope of the present disclosure. By using such additives, the properties of the fluororesin layer (F), such as surface hardness, abrasion resistance, electrostatic property, weather resistance, etc., can be improved.
[0109] When the laminate of the present disclosure includes a fluororesin layer (F), it is preferable that the fluororesin layer (F) is configured to come into contact with fuel. By forming the contact surface between the laminate and the fuel with the fluororesin layer (F), excellent fuel resistance is imparted to the laminate, and durability of the laminate is improved. In addition, when the fluororesin layer (F) has electrical conductivity, by forming the contact surface between the laminate and the fuel with the fluororesin layer (F), charging of the laminate can be further prevented even if static electricity is generated due to friction between the laminate and the fuel.
[0110] (Non-fluorinated polymer (N2)) The laminate of the present disclosure may further include a non-fluorinated polymer layer (N2) that is not electrically conductive and contains a non-fluorinated polymer (N2) (excluding the non-fluorinated polymer (A)). The non-fluorinated polymer (N2) is a non-fluorinated polymer other than an ethylene / vinyl alcohol copolymer and an aromatic polyamide.
[0111] As the non-fluorinated polymer (N2), a wide variety of polymers known as thermoplastic resins other than ethylene / vinyl alcohol copolymers and aromatic polyamides can be used. Examples of the non-fluorinated polymer (N2) include aliphatic polyamide resins, polyolefin resins, vinyl chloride resins, polyurethane resins, polyester resins, polyaramid resins, polyimide resins, polyamideimide resins, polyphenylene oxide resins, polyacetal resins, polycarbonate resins, acrylic resins, styrene resins, acrylonitrile / butadiene / styrene resins (ABS), cellulose resins, polyether ether ketone resins (PEEK), polysulfone resins, polyether sulfone resins (PES), polyetherimide resins, polyphenylene sulfide resins, polybutylene naphthalate resins, polybutylene terephthalate resins, and polyphthalamide (PPA).
[0112] The melting point of the non-fluorinated polymer (N2) is preferably 50°C or higher, more preferably 100°C or higher, even more preferably 150°C or higher, and preferably 400°C or lower, more preferably 300°C or lower, even more preferably 250°C or lower.
[0113] As the non-fluorinated polymer (N2), among others, at least one selected from the group consisting of an aliphatic polyamide resin and a polyolefin resin is preferable, and an aliphatic polyamide resin is more preferable.
[0114] Aliphatic polyamide resins are what are known as nylon resins, which are made of polymers in which an amide bond in the molecule is bonded to an aliphatic structure or an alicyclic structure.
[0115] The aliphatic polyamide resin (nylon resin) is not particularly limited, and examples thereof include polyamide 6, polyamide 66, polyamide 11, polyamide 12, polyamide 610, polyamide 1010, polyamide 612, polyamide 6 / 66, polyamide 66 / 12, polyamide 46, metaxylylenediamine / adipic acid copolymer, polyamide 62, polyamide 92, polyamide 122, and polyamide 142.
[0116] The aliphatic polyamide resin may also be a polymer in which a structure having no amide bond as a repeating unit is block-copolymerized or graft-copolymerized in a part of the molecule. Examples of such aliphatic polyamide resins include polyamide-based elastomers such as polyamide 6 / polyester copolymer, polyamide 6 / polyether copolymer, polyamide 12 / polyester copolymer, and polyamide 12 / polyether copolymer. These polyamide-based elastomers are obtained by block-copolymerizing a polyamide oligomer and a polyester oligomer via an ester bond, or by block-copolymerizing a polyamide oligomer and a polyether oligomer via an ether bond. Examples of the polyester oligomer include polycaprolactone and polyethylene adipate, and examples of the polyether oligomer include polyethylene glycol, polypropylene glycol, and polytetramethylene glycol. Examples of the polyamide-based elastomers include polyamide 6 / polytetramethylene glycol copolymer and polyamide 12 / polytetramethylene glycol copolymer.
[0117] As the aliphatic polyamide resin, since a layer made of aliphatic polyamide resin can obtain sufficient mechanical strength even in a thin layer, at least one selected from the group consisting of polyamide 6, polyamide 66, polyamide 11, polyamide 12, polyamide 610, polyamide 1010, polyamide 612, polyamide 62, polyamide 6 / 66, polyamide 66 / 12, polyamide 6 / polyester copolymer, polyamide 6 / polyether copolymer, polyamide 12 / polyester copolymer and polyamide 12 / polyether copolymer is preferred, and at least one selected from the group consisting of polyamide 11, polyamide 12 and polyamide 612 is more preferred.
[0118] The polyolefin resin is a resin having monomer units derived from a vinyl group-containing monomer that does not have a fluorine atom.
[0119] The polyolefin resin is not particularly limited, and examples thereof include polyolefins such as polyethylene, polypropylene, high-density polyolefins, and low-density polyolefins, as well as modified polyolefins obtained by modifying the above-mentioned polyolefins with maleic anhydride or the like, epoxy-modified polyolefins, and amine-modified polyolefins, among which high-density polyolefins are preferred.
[0120] The non-fluorinated polymer layer (N2) may contain additives other than the conductive filler, such as various additives such as reinforcing agents, bulking agents, ultraviolet absorbers, pigments, etc., within the scope of the present disclosure. By using such additives, the properties of the non-fluorinated polymer layer (N2), such as surface hardness, abrasion resistance, electrostatic property, weather resistance, etc., can be improved.
[0121] The non-fluorinated polymer layer (N2) does not have electrical conductivity. The non-fluorinated polymer layer (N2) does not contain a conductive filler.
[0122] (Structure of Laminate) The laminate of the present disclosure includes at least a non-fluorinated polymer layer (A) containing at least one non-fluorinated polymer (A) selected from the group consisting of ethylene / vinyl alcohol copolymers and aromatic polyamides. The number of layers of the laminate of the present disclosure is not particularly limited as long as it is 2 or more. The number of layers of the laminate of the present disclosure may be 2 to 5.
[0123] The laminate of the present disclosure may include a polymer layer (B) containing a polymer (excluding the non-fluorinated polymer layer (A)) in addition to the non-fluorinated polymer layer (A). Examples of the polymer layer (B) include a conductive layer (N1), a fluororesin layer (F), and a non-fluorinated polymer layer (N2).
[0124] In the laminate of the present disclosure, the non-fluorinated polymer layer (A) and the polymer layer (B) may be directly bonded to each other or may be bonded to each other via another layer such as an adhesive layer, but it is preferable that they are directly bonded to each other.
[0125] The laminate of the present disclosure includes a laminate comprising at least a conductive layer (N1) and a non-fluorinated polymer layer (A), and a laminate comprising at least a fluororesin layer (F) and a non-fluorinated polymer layer (A).
[0126] The laminate of the present disclosure is, for example, A laminate having a conductive layer (N1) / a non-fluorinated polymer layer (A) as an innermost layer / an outermost layer, a laminate having a fluororesin layer (F) / a non-fluorinated polymer layer (A), A laminate having a conductive layer (N1) / a non-fluorinated polymer layer (A) / a non-fluorinated polymer layer (N2) as an innermost layer / an intermediate layer / an outermost layer, a laminate having a fluororesin layer (F) / a non-fluorinated polymer layer (A) / a non-fluorinated polymer layer (N2); A laminate comprising an electrically conductive layer (N1) / a non-fluorinated polymer layer (N2) / a non-fluorinated polymer layer (A) / a non-fluorinated polymer layer (N2) as an innermost layer / an inner layer / an intermediate layer / an outermost layer; a laminate comprising a fluororesin layer (F) / a non-fluorinated polymer layer (N2) / a non-fluorinated polymer layer (A) / a non-fluorinated polymer layer (N2); a laminate comprising, as an innermost layer / inner layer / middle layer / outer layer / outermost layer, a conductive layer (N1) / a non-fluorinated polymer layer (N2) / a non-fluorinated polymer layer (A) / a non-fluorinated polymer layer (N2) / a non-fluorinated polymer layer (N2); a laminate comprising, as an innermost layer / inner layer / middle layer / outer layer / outermost layer, a conductive layer (N1) / a non-fluorinated polymer layer (N2) / a non-fluorinated polymer layer (A) / a non-fluorinated polymer layer (N2) / a non-fluorinated polymer layer (N2); etc.
[0127] When the laminate of the present disclosure has two or more non-fluorinated polymer layers (A), the type of non-fluorinated polymer (A) contained in each layer may be the same or different. When the laminate of the present disclosure has two or more conductive layers (N1), the type of non-fluorinated polymer (N1) contained in each layer may be the same or different. When the laminate of the present disclosure has two or more fluororesin layers (F), the type of fluororesin contained in each layer may be the same or different. When the laminate of the present disclosure has two or more non-fluorinated polymer layers (N2), the type of non-fluorinated polymer (N2) contained in each layer may be the same or different. In the laminate of the present disclosure, the boundary between the adjacent layers is not necessarily clear, and the molecular chains of the polymers constituting each layer may penetrate each other from the contact surface, and a layer structure with a concentration gradient may be formed.
[0128] The laminate of the present disclosure may have other layers. The thickness, shape, etc. of each layer of the laminate of the present disclosure may be appropriately selected depending on the purpose and form of use.
[0129] The laminate of the present disclosure preferably has a fuel permeation rate of 15 g / m 2 / day or less, and more preferably 10 g / m 2 / day or less, and more preferably 5.0 g / m 2 / day or less, and particularly preferably 3.0 g / m 2 / day or less. When the fuel contains alcohol, the fuel permeation rate of the laminate of the present disclosure is preferably 15 g / m 2 / day or less, and more preferably 10 g / m 2 / day or less, and more preferably 5.0 g / m 2 / day or less, and particularly preferably 3.0 g / m 2 / day or less. When the fuel contains gasoline, the fuel permeation rate of the laminate of the present disclosure is preferably 15 g / m 2 / day or less, and more preferably 10 g / m 2 / day or less, and more preferably 5.0 g / m 2 / day or less, and particularly preferably 3.0 g / m 2 / day or less. When the fuel contains diesel fuel (light oil), the fuel permeation rate of the laminate of the present disclosure is preferably 8.0 g / m 2 / day or less, and more preferably 5.0 g / m 2 / day or less, and more preferably 3.0 g / m 2 / day or less.
[0130] The fuel permeation rate of the laminate is the rate at which a fuel containing at least the compound (1) consisting of only carbon atoms, hydrogen atoms, and oxygen atoms and having a carbonyl group or an ether bond permeates the laminate. The fuel permeation rate of the laminate can be determined by preparing a tubular laminate, preparing a fuel containing the compound (1) at a predetermined concentration, sealing the fuel in the tubular laminate, leaving it at 60°C or 80°C, measuring the mass change per hour, and calculating the fuel permeation rate from the mass change and the inner area of the tubular laminate. When the fuel contains alcohol or gasoline, the fuel can be sealed in the tubular laminate and left at 60°C, and then the mass change per hour can be measured. When the fuel contains diesel fuel (light oil), the fuel can be sealed in the tubular laminate and left at 80°C, and then the mass change per hour can be measured.
[0131] The laminate of the present disclosure can be in various shapes such as a film shape, a sheet shape, a tube (hose) shape, a bottle shape, a tank shape, etc. The film shape, sheet shape, tube shape, and hose shape may be a corrugated shape, a corrugated shape, a convoluted shape, etc. The laminate of the present disclosure may be, for example, a film, a sheet, a tube, a hose, a bottle, a container, a tank, etc. The laminate of the present disclosure can be suitably used for, for example, a fuel tube or a fuel hose such as an automobile fuel tube or an automobile fuel hose, an underground buried tube or hose for a fuel supply facility, an automobile fuel tank, various automobile seals such as an O-ring for a fuel pump, etc.
[0132] In one embodiment, the laminate of the present disclosure is used as a member constituting a system for distributing fuel that is composed of only carbon atoms, hydrogen atoms, and oxygen atoms and contains at least a compound (1) having a carbonyl group or an ether bond. The system for distributing fuel is, for example, a system used for storing or supplying fuel. Members used in such a system include tanks, tubes, hoses, caps, valves, diaphragms, seals (O-rings), and the like. The system for distributing fuel is, for example, not only used in automobiles, but also in facilities for supplying fuel to automobile fuel tanks. A typical example of a member constituting a system for distributing fuel is a fuel tube or a fuel hose.
[0133] (Tubes and Hoses) The laminate of the present disclosure can be suitably used as a tube or a hose. In the present disclosure, the term "tube or hose" includes an article generally called a tube or a hose, and is usually an article having a shape capable of transporting a fluid. In the present disclosure, the term "tube or hose" does not mean that a tube and a hose are different articles.
[0134] The tube or hose of the present disclosure may have the same configuration as the laminate described above.
[0135] The fuel permeation rate of the tube or hose of the present disclosure is preferably 15 g / m 2 / day or less, and more preferably 10 g / m 2 / day or less, and more preferably 5.0 g / m 2 / day or less, and particularly preferably 3.0 g / m 2 / day or less. When the fuel contains alcohol, the fuel permeation rate of the tube or hose of the present disclosure is preferably 15 g / m 2 / day or less, and more preferably 10 g / m 2 / day or less, and more preferably 5.0 g / m 2 / day or less, and particularly preferably 3.0 g / m 2 / day or less. When the fuel contains gasoline, the fuel permeation rate of the tube or hose of the present disclosure is preferably 15 g / m 2 / day or less, and more preferably 10 g / m 2 / day or less, and more preferably 5.0 g / m 2 / day or less, and particularly preferably 3.0 g / m 2 / day or less. When the fuel contains diesel fuel (light oil), the fuel permeation rate of the tube or hose of the present disclosure is preferably 8.0 g / m 2 / day or less, and more preferably 5.0 g / m 2 / day or less, and more preferably 3.0 g / m 2 / day or less.
[0136] The fuel permeation rate of a tube or hose is the rate at which a fuel containing at least compound (1) consisting of only carbon atoms, hydrogen atoms, and oxygen atoms and having a carbonyl group or an ether bond permeates through the tube or hose. The fuel permeation rate of a tube or hose can be determined by preparing a fuel containing compound (1) at a predetermined concentration, sealing the fuel in a tube or hose, leaving it at 60°C or 80°C, measuring the mass change per hour, and calculating the fuel permeation rate from the mass change and the inner area of the tube or hose. When the fuel contains alcohol or gasoline, the fuel can be sealed in a tube or hose and left at 60°C, and the mass change per hour can be measured. When the fuel contains diesel fuel (light oil), the fuel can be sealed in a tube or hose and left at 80°C, and the mass change per hour can be measured.
[0137] The outer diameter of the tube or hose is preferably 2 mm or more, more preferably 3 mm or more, even more preferably 4 mm or more, and most preferably 6 mm or more, and is preferably 20 mm or less, more preferably 18 mm or less, even more preferably 16 mm or less, and most preferably 14 mm or less.
[0138] The inner diameter of the tube or hose is preferably 1 mm or more, more preferably 2 mm or more, even more preferably 3 mm or more, and most preferably 4 mm or more, and is preferably 15 mm or less, more preferably 13 mm or less, even more preferably 11 mm or less, and most preferably 10 mm or less.
[0139] The thickness of the tube or hose (the difference between the outer diameter and the inner diameter) is preferably 0.5 mm or more, more preferably 0.6 mm or more, even more preferably 0.7 mm or more, and preferably 8 mm or less, more preferably 6 mm or less, even more preferably 4 mm or less, and particularly preferably 2 mm or less.
[0140] The thickness of the non-fluorinated polymer layer (A) in the laminate and the tube or hose is preferably 0.05 mm or more, more preferably 0.10 mm or more, even more preferably 0.15 mm or more, and preferably 0.40 mm or less, more preferably 0.30 mm or less, even more preferably 0.20 mm or less. When the laminate and the tube or hose have two or more non-fluorinated polymer layers (A), the thickness of the non-fluorinated polymer layer (A) is the total thickness of the layers.
[0141] The thickness of the polymer layer (B) in the laminate and the tube or hose is preferably 0.10 mm or more, more preferably 0.20 mm or more, even more preferably 0.30 mm or more, and preferably 0.90 mm or less, more preferably 0.80 mm or less, and even more preferably 0.70 mm or less. When the laminate and the tube or hose have two or more polymer layers (B), the thickness of the polymer layer (B) is the total thickness of the layers.
[0142] The thickness of the conductive layer (N1) in the laminate and the tube or hose is preferably 0.05 mm or more, more preferably 0.10 mm or more, and preferably 0.40 mm or less, more preferably 0.30 mm or less, and even more preferably 0.20 mm or less. When the laminate and the tube or hose have two or more conductive layers (N1), the thickness of the conductive layer (N1) is the total thickness of the layers.
[0143] The thickness of the fluororesin layer (F) in the laminate and the tube or hose is preferably 0.05 mm or more, more preferably 0.10 mm or more, and preferably 0.40 mm or less, more preferably 0.30 mm or less, and even more preferably 0.20 mm or less. When the laminate and the tube or hose have two or more fluororesin layers (F), the thickness of the fluororesin layer (F) is the total thickness of the layers.
[0144] The thickness of the non-fluorinated polymer layer (N2) in the laminate and the tube or hose is preferably 0.10 mm or more, more preferably 0.20 mm or more, even more preferably 0.30 mm or more, and preferably 0.90 mm or less, more preferably 0.80 mm or less, even more preferably 0.70 mm or less. When the laminate and the tube or hose have two or more non-fluorinated polymer layers (N2), the thickness of the non-fluorinated polymer layer (N2) is the total thickness of the layers.
[0145] The tube or hose may be corrugated, corrugated, convoluted, etc. When the tube or hose has a corrugated shape, it has an area with a plurality of corrugated folds arranged in an annular shape, which allows one side of the annular shape to be compressed and the other side to be stretched outward, allowing it to be easily bent to any angle without stress fatigue or delamination.
[0146] There is no particular limitation on the method for forming the corrugated region, but it can be easily formed by forming a straight tube or hose, and then subsequently molding the tube or hose to give it a predetermined corrugated shape.
[0147] The method for producing the laminate of the present disclosure includes, for example, (1) A method of forming a multi-layered laminate in one step by co-extrusion molding the polymers that form each layer and heat-sealing (melting and bonding) the layers together (co-extrusion molding); (2) A method in which each layer is produced separately using an extruder, and then the layers are laminated together and bonded by heat fusion. (3) A method of forming a laminate by extruding a polymer for forming a layer adjacent to a previously prepared layer onto the surface of the previously prepared layer using an extruder; (4) A method in which a polymer that will form a layer adjacent to a previously prepared layer is electrostatically coated on the surface of the layer, and the resulting coated product is heated overall or from the coated side to heat and melt the coated polymer and form a layer. etc.
[0148] When the laminate of the present disclosure is a tube or a hose, examples of the method corresponding to the above (2) include (2a) a method in which each cylindrical layer is separately formed by an extruder, and a layer that comes into contact with the layer that will become the inner layer is coated with a heat-shrinkable tube; a method corresponding to the above (3) includes (3a) a method in which a layer that will become the inner layer is first formed by an inner layer extruder, and a layer that comes into contact with the inner layer is formed on the outer surface of the inner layer by an outer layer extruder; and a method corresponding to the above (4) includes (4a) a method in which a polymer that constitutes the inner layer is electrostatically coated on the inside of a layer that will come into contact with the inner layer, and the resulting coated article is placed in a heating oven and heated overall, or a rod-shaped heating device is inserted inside a cylindrical coated article and heated from the inside, thereby heating and melting the polymer that constitutes the inner layer to form the article.
[0149] If the layers constituting the laminate and tube or hose of the present disclosure are coextrudable, they are generally formed by the coextrusion molding method (1) above. Examples of the coextrusion molding include conventionally known multilayer coextrusion manufacturing methods such as the multi-manifold method and the feed block method.
[0150] In the above molding methods (2) and (3), after each layer is formed, the contact surface of each layer with other layers may be surface-treated in order to enhance interlayer adhesion. Examples of such surface treatments include etching treatments such as sodium etching treatment, corona treatments, and plasma treatments such as low-temperature plasma treatments.
[0151] The laminate of the present disclosure may also be formed by laminating multiple materials in multiple stages by rotational molding. In this case, the melting point of the outer layer material does not necessarily have to be higher than that of the inner layer material, and the melting point of the inner layer material may be 100° C. or more higher than that of the outer layer material. In this case, it is preferable to have a heating section inside as well.
[0152] The tube or hose of the present disclosure can be suitably used, for example, as a fuel tube or fuel hose, such as an automobile fuel tube or automobile fuel hose, or an underground buried tube or hose for a fuel supply facility.
[0153] Although the embodiments have been described above, it will be understood that various changes in form and details are possible without departing from the spirit and scope of the claims.
[0154] <1> According to a first aspect of the present disclosure, A laminate in contact with a fuel, comprising: The fuel contains at least a compound (1) consisting of only carbon atoms, hydrogen atoms, and oxygen atoms and having a carbonyl group or an ether bond; The laminate includes at least a non-fluorinated polymer layer containing at least one non-fluorinated polymer selected from the group consisting of an ethylene / vinyl alcohol copolymer and an aromatic polyamide. <2> According to a second aspect of the present disclosure, There is provided a laminate according to a first aspect, wherein the compound (1) is at least one selected from the group consisting of a carbonate ester, a chain ether, and a cyclic ether. <3> According to a third aspect of the present disclosure, There is provided a laminate according to the first or second aspect, wherein compound (1) is at least one selected from the group consisting of dimethyl carbonate, diethyl carbonate, dimethyl ether, methyl tert-butyl ether, oxymethylene dimethyl ether and 1-3 dioxolane. <4> According to a fourth aspect of the present disclosure, There is provided a laminate according to any one of the first to third aspects, wherein the fuel further contains alcohol. <5> According to a fifth aspect of the present disclosure, There is provided a laminate according to any one of the first to fourth aspects, wherein the fuel further contains gasoline. <6> According to a sixth aspect of the present disclosure, There is provided a laminate according to any one of the first to fifth aspects, wherein the fuel further contains diesel fuel. <7> According to a seventh aspect of the present disclosure, The laminate according to any one of the first to sixth aspects is provided, wherein the content of compound (1) in the fuel is 0.1 to 20% by volume. <8> According to an eighth aspect of the present disclosure, There is provided a laminate according to any one of the first to seventh aspects, wherein the non-fluorinated polymer layer has a thickness of 0.05 to 0.40 mm. <9> According to a ninth aspect of the present disclosure, There is provided a laminate according to any one of the first to eighth aspects, which further comprises a conductive layer having electrical conductivity and containing a non-fluorinated polymer. <10> According to a tenth aspect of the present disclosure, There is provided a laminate according to a ninth aspect, wherein the non-fluorinated polymer is an aromatic polyamide. <11> According to an eleventh aspect of the present disclosure, According to the ninth or tenth aspect there is provided a laminate, wherein the conductive layer is in contact with the fuel. <12> According to a twelfth aspect of the present disclosure, There is provided a laminate according to any one of the first to eleventh aspects, further comprising a fluororesin layer containing a fluororesin. <13> According to a thirteenth aspect of the present disclosure, According to a twelfth aspect, there is provided a laminate, wherein the fluororesin is at least one selected from the group consisting of fluororesins containing ethylene units and tetrafluoroethylene units, and fluororesins containing chlorotrifluoroethylene units and tetrafluoroethylene units. <14> According to a fourteenth aspect of the present disclosure, According to a twelfth or thirteenth aspect, there is provided a laminate, wherein the fluororesin layer has electrical conductivity. <15> According to a fifteenth aspect of the present disclosure, According to any one of the twelfth to fourteenth aspects, there is provided a laminate, wherein the fluororesin layer is in contact with the fuel. <16> According to a sixteenth aspect of the present disclosure, The fuel permeation rate is 15 g / m 2 / day or less according to any one of the first to fifteenth aspects. <17> According to a seventeenth aspect of the present disclosure, There is provided a tube or hose formed from the laminate according to any one of the first to sixteenth aspects. <18> According to an eighteenth aspect of the present disclosure, A tube or hose formed from the laminate according to any one of the first to eleventh and sixteenth aspects, The laminate comprises: A conductive layer (N1) containing a conductive filler and an aromatic polyamide; A non-fluorinated polymer layer (A) containing an aromatic polyamide, and Non-fluorinated polymer layer containing aliphatic polyamide resin (N2) In this order, The conductive layer (N1) is the innermost layer and is in contact with the fuel. A tube or hose is provided. <19> According to a nineteenth aspect of the present disclosure, A tube or hose formed from the laminate according to any one of the first to eighth and twelfth to sixteenth aspects, The laminate comprises: A fluororesin layer (F) containing a conductive filler and a fluororesin containing an ethylene unit and a tetrafluoroethylene unit; A non-fluorinated polymer layer (N2) containing an aliphatic polyamide resin; A non-fluorinated polymer layer (A) containing an ethylene / vinyl alcohol copolymer; a non-fluorinated polymer layer (N2) containing an aliphatic polyamide resin, and Non-fluorinated polymer layer containing aliphatic polyamide resin (N2) In this order, The fluororesin layer (F) is the innermost layer and comes into contact with the fuel. A tube or hose is provided. EXAMPLES
[0155] Next, embodiments of the present disclosure will be described with reference to examples, but the present disclosure is not limited to these examples.
[0156] The values in the examples were measured by the following methods.
[0157] <Polymer composition (monomer composition of fluororesin)> Using a nuclear magnetic resonance spectrometer AC300 (manufactured by Bruker-Biospin), 19 F-NMR measurements were performed, and the monomer composition of the fluororesin (content of each monomer unit in the polymer) was calculated from the integral value of each peak. Depending on the type of monomer, the results of elemental analysis were appropriately combined to determine the monomer composition of the fluororesin.
[0158] <Melting point> Using a differential scanning calorimeter RDC220 (Seiko Instruments), heat measurement was carried out at a temperature increase rate of 10° C. / min in accordance with ASTM D 4591, and the melting point of the fluororesin was determined from the peak of the obtained endothermic curve.
[0159] <Melt flow rate (MFR)> Using a melt indexer (manufactured by Yasuda Seiki Seisakusho), the mass (g / 10 min) of the fluororesin flowing out per 10 min from a nozzle with an inner diameter of 2 mm and a length of 8 mm at 265°C or 297°C under a load of 5 kg was determined as the MFR in accordance with ASTM D 1238.
[0160] <Fuel permeation rate> The tubes obtained in the experimental and comparative experimental examples were cut and the inside diameter and length were measured. Swagelok fittings were attached to both ends of the tube, the tube was filled with the following fuel, the lid was tightened, and the mass of the tube with the fuel sealed inside was measured. The tube was then kept at 60°C or 80°C, and the mass was measured after 1000 hours had passed. The amount of mass loss was calculated from each measured mass, and the fuel permeation rate (g / m2) was calculated from the amount of mass loss and the inner area of the tube. 2 / day) was calculated.
[0161] The following fuels were used to measure the fuel permeation rate: CE10 (toluene / isooctane / ethanol = 45 / 45 / 10% by volume), CM15 (toluene / isooctane / methanol = 42.5 / 42.5 / 15% by volume), Fuel C (toluene / isooctane = 50 / 50% by volume), E (ethanol), M (methanol), and DMC (dimethyl carbonate) in arbitrary ratios. When using these fuels, the tube was kept at 60°C, and the mass was measured after 1000 hours to calculate the fuel permeation rate. Fuel (1): CE10 100% by volume Fuel (2): Fuel C / E / DMC = 85 / 10 / 5 (volume%) Fuel (3): Fuel C / E / DMC = 80 / 10 / 10 (volume%) Fuel (4): Fuel C / E / DMC = 70 / 10 / 20 (volume%) Fuel (5): E / DMC=10 / 90 (volume%) Fuel (6): DMC 100% by volume Fuel (7): CM15 100% by volume Fuel (8): Fuel C / M / DMC = 65 / 15 / 20 (volume%)
[0162] The fuel permeation rate was measured using the following fuels, each containing diesel and DMC (dimethyl carbonate) in a given ratio: When using these fuels, the tube was kept at 80°C, and the mass was measured after 1000 hours to calculate the fuel permeation rate. Fuel (1): diesel 100% by volume Fuel (2): diesel / DMC=95 / 5 (volume%) Fuel (3): diesel / DMC=90 / 10 (volume%) Fuel (4): diesel / DMC=80 / 20 (volume%)
[0163] The following materials were used in the experimental examples and comparative experimental examples.
[0164] Conductive polyamide 9T (PA9T cond.) Kuraray, Genestar TS341 Polyamide 9T (PA9T) Kuraray, Genestar N1001D
[0165] Fluorine Resin A Polymer composition (mol%): TFE / Et / HFP / 2,3,3,4,4,5,5-heptafluoro-1-pentene) = 45.5 / 44.4 / 9.5 / 0.6 Melting point: 197℃ Melt flow rate (265℃): 5.0g / 10min Carbon black content: 12% by mass
[0166] Ethylene / vinyl alcohol copolymer (EVOH) Kuraray, F101B
[0167] Polyamide 12 (PA12) Polypla-Evonik, Daiamid X7297 Polyamide 612 (PA612) Evonik, VESTAMID SX8002
[0168] Experimental Examples 1-2 and Comparative Experimental Example 1 Using a five-type, five-layer tube extrusion device equipped with a multi-manifold (manufactured by Plastics Engineering Research Institute), each material was supplied to the extruder so that each layer was composed of the material listed in Table 1, and a multi-layer tube with an outer diameter of 8 mm and an inner diameter of 6 mm was molded.
[0169] The physical properties of the resulting multilayer tube were measured by the methods described above. The results are shown in Table 2.
[0170] [Table 1]
[0171] [Table 2]
[0172] Experimental Examples 3-4 and Comparative Experimental Examples 2-3 Using a five-type, five-layer tube extrusion device equipped with a multi-manifold (manufactured by Plastics Engineering Research Institute), each material was supplied to the extruder so that each layer was composed of the material listed in Table 1, and a multi-layer tube with an outer diameter of 8 mm and an inner diameter of 6 mm was molded.
[0173] The physical properties of the resulting multilayer tube were measured by the methods described above. The results are shown in Table 2.
[0174] [Table 3]
[0175] [Table 4]
Claims
1. A laminate in contact with a fuel, comprising: The fuel contains at least a compound (1) consisting of only carbon atoms, hydrogen atoms, and oxygen atoms and having a carbonyl group or an ether bond; The laminate comprises at least a non-fluorinated polymer layer containing at least one non-fluorinated polymer selected from the group consisting of ethylene / vinyl alcohol copolymers and aromatic polyamides.
2. 2. The laminate according to claim 1, wherein the compound (1) is at least one selected from the group consisting of carbonate esters, chain ethers, and cyclic ethers.
3. 3. The laminate according to claim 1, wherein the compound (1) is at least one selected from the group consisting of dimethyl carbonate, diethyl carbonate, dimethyl ether, methyl tert-butyl ether, oxymethylene dimethyl ether and 1-3 dioxolane.
4. 3. The laminate according to claim 1, wherein the fuel further comprises an alcohol.
5. 3. The laminate of claim 1 or 2, wherein the fuel further comprises gasoline.
6. 3. The laminate of claim 1 or 2, wherein the fuel further comprises diesel fuel.
7. 3. The laminate according to claim 1, wherein the content of the compound (1) in the fuel is 0.1 to 20% by volume.
8. 3. The laminate according to claim 1, wherein the non-fluorinated polymer layer has a thickness of 0.05 to 0.40 mm.
9. 3. The laminate according to claim 1 or 2, further comprising a conductive layer having electrical conductivity and containing a non-fluorinated polymer.
10. 10. The laminate of claim 9, wherein the non-fluorinated polymer is an aromatic polyamide.
11. 10. The stack of claim 9, wherein the conductive layer is in contact with the fuel.
12. The laminate according to claim 1 or 2, further comprising a fluororesin layer containing a fluororesin.
13. 13. The laminate according to claim 12, wherein the fluororesin is at least one selected from the group consisting of fluororesins containing ethylene units and tetrafluoroethylene units, and fluororesins containing chlorotrifluoroethylene units and tetrafluoroethylene units.
14. The laminate according to claim 12 , wherein the fluororesin layer is electrically conductive.
15. The laminate according to claim 12 , wherein the fluororesin layer is in contact with the fuel.
16. The fuel permeation rate is 15 g / m 2 3. The laminate according to claim 1 or 2, wherein the average molecular weight is 10 ...
17. A tube or hose formed from the laminate of claim 1 or 2.
18. A tube or hose formed from the laminate of claim 1 or 2, The laminate comprises: A conductive layer (N1) containing a conductive filler and an aromatic polyamide; a non-fluorinated polymer layer (A) containing an aromatic polyamide; and a non-fluorinated polymer layer (N2) containing an aliphatic polyamide resin; In this order, The conductive layer (N1) is the innermost layer and is in contact with the fuel. Tube or hose.
19. A tube or hose formed from the laminate of claim 1 or 2, The laminate comprises: A fluororesin layer (F) containing a conductive filler and a fluororesin containing an ethylene unit and a tetrafluoroethylene unit; a non-fluorinated polymer layer (N2) containing an aliphatic polyamide resin; A non-fluorinated polymer layer (A) containing an ethylene / vinyl alcohol copolymer; A non-fluorinated polymer layer (N2) containing an aliphatic polyamide resin, and a non-fluorinated polymer layer (N2) containing an aliphatic polyamide resin; In this order, The fluororesin layer (F) is the innermost layer and comes into contact with the fuel. Tube or hose.
Citation Information
Patent Citations
Electroconductive laminate tube
JP2014240148A
Laminated tube
JP2017193101A
Laminate tube
JP2020112261A
Tube for fuel and production method of the same
JP2022044082A
Laminated resin formed body and method for producing same
WO2004069534A1